PENGGUNAAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN SENI BUDAYA DI SMA NEGERI 12 PADANG - Cahyani, Nining Dwi; Yensharti, Yensharti (SENDRATASIK UNP, 2019)
AbstractÂ The study aims to determine whether there are differences in students learning outcomes that is taught using audiovisual media with students learning outcomes without using audiovisual media in learning music art in SMA Negeri 12 Padang. The type of study was quantitative with experimental methods. The design in this study used Pretest-posttest control Group Design. Sample in this study was determined by cluster sampling technique, and samples were obtainedfrom class XI IPS 1 as an experimental class and class XI IPS2 as a control class. Both two variables, namely the use of audiovisual and conventional media, while therelated variables were students learning outcomes in cultural art subject. The data was obtained from multiple choice tests of western music material on the pretest and posttest. The validity test used theproduct momentformulaand the reliability test used the Alpha formula. Technique of data analysis was done by using t-test. Data was obtained from the pretest and posttest results.Then, it processes using Microsoft Excel 2010. The result of this study indicates that the learning outcomes of the experimental class that is using audiovisual media are better than the learning outcomes of the control class that is using conventional media. There is a significant difference between learning outcomes taught by using audiovisual media and learning outcomes that use conventional media in cultural art learning. This is evidenced by the t-test calculation values that is obtainedthat thitung= 2.208 and ttable= 2.012. The use of audiovisual media in cultural art learning can improve students learning outcomes for the better, this is evidenced from the increase in the average learning outcomes of experimental class students is 83.20 and the average control class is 77.609. Thus,it is obtained an average difference between the experimental and the control classesnamely 5.591.Â Keywords: Usage, AudioVisual Media, Cultural Art Learning.